Projeto arquitetônico de uma casa flutuante para os rios da Amazônia - CUNHA, Emerson Pena da (2019)
The constructive potential on the waters of rivers in the Amazon is the object of study addressed in this work. It is proposed a model of floating house suitable to the local and global contexts for the present moment and for the perspectives of future. An architectural project was designed to offer alternatives of viable floating construction, with solutions to the usual problem of floods and landslides of ravines on the banks of the rivers of the region. It is an ecologically correct project, economically feasible and defined as a constructive proposal in view of the precariousness found in riverside buildings in the region. This project provides for the permanent use of the house by users throughout the year in the same place and has a streamlined construction system, adequate sewage treatment, thermal comfort and use of rainwater.